Tocotrienol-rich fraction (TRF) improves the viability of wild-type Saccharomyces cerevisiae in the initial stationary phase - Khaizurin Tajul Arifin,; Tuan, Sheng G; Muhammed Whisz QR,; Blitzer BM,; Saidatul Akmaliah A,; Nurliza AJ,; Pei, Jia L; Rachael Shristi W, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Palm oil tocotrienol-rich fraction (TRF) containing majorly of αα, β, γ andδδ-tocotrienols and some αα-tocopherols, was reported to have anti-ageing effects in both human and non-human model organisms, but still remains unexplored in the yeast model. It was reported to have the ability to extend the lifespan of several organisms. Chronological lifespan is one of the means to measure ageing in yeasts. The effect of TRF on the viability of three strains of Saccharomyces cerevisiae (wild-type, CTT1ΔΔand GPx2Δ) was studied. Phenotypic growth analysis of all strains was carried out for 15 hours by measuring the absorbance at OD600nm and cell counting. The optimum dose of TRF was optimised by determining the number of colony-forming unit by the wild-type strain at the end of a 24-hour treatment with TRF (ranging from 0μg/ml to 300μg/ml). TRF at 300 μg/mL showed the best result, and selected as a working dose. Treatment of cells with 300 μg/mL of TRF improved the viability of the wild-type strain in the initial stationary phase, but not on the knockout strains. These finding suggests that TRF has a potential in prolonging the chronological lifespan of S. cerevisiae, and perhaps other organisms as well.